Dendrimers as Non-Viral Vectors in Gene-Directed Enzyme Prodrug Therapy - Adriana Aurelia Chis; Carmen Maximiliana Dobrea; Luca-Liviu Rus; Adina Frum; Claudiu Morgovan; Anca Butuca; Maria Totan; Anca Maria Juncan; Felicia Gabriela Gligor; Anca Maria Arseniu (Molecules, 2021)
Gene-directed enzyme prodrug therapy (GDEPT) has been intensively studied as a promising new strategy of prodrug delivery, with its main advantages being represented by an enhanced efficacy and a reduced off-target toxicity of the active drug. In recent years, numerous therapeutic systems based on GDEPT strategy have entered clinical trials. In order to deliver the desired gene at a specific site of action, this therapeutic approach uses vectors divided in two major categories, viral vectors and non-viral vectors, with the latter being represented by chemical delivery agents. There is considerable interest in the development of non-viral vectors due to their decreased immunogenicity, higher specificity, ease of synthesis and greater flexibility for subsequent modulations. Dendrimers used as delivery vehicles offer many advantages, such as: nanoscale size, precise molecular weight, increased solubility, high load capacity, high bioavailability and low immunogenicity. The aim of the present work was to provide a comprehensive overview of the recent advances regarding the use of dendrimers as non-viral carriers in the GDEPT therapy.